Effectiveness of Baby Massage on the Growth and Development of Toddlers: A Scoping Review - Heriyanti, Silvia Widyani; Purnamasari, Kurniati Devi; Suminar, Ratna (JURNAL KESEHATAN POLTEKKES KEMENKES RI PANGKALPINANG, 2025)
Background: Infancy and toddlerhood are important periods in a child's growth and development that require special attention. Baby massage, as a form of communication through touch, is beneficial for growth and development. Regular massage can help increase weight, improve sleep quality, and stimulate the digestive system, which can lead to an increased appetite. In addition to providing a relaxing and comfortable effect, baby massage strengthens the emotional bond between mother and child. Therefore, mothers need to understand the techniques and benefits of baby massage as a form of stimulation and affection through gentle touch.Aim: This Scoping review analyzes the effectiveness of infant massage on infant growth and development.Method: This article's Scoping review uses the PRISMA method to identify articles published during the last five years (2019-2023) through Google Scholar, SAGE, Science Direct, and PubMed and produces 8 relevant journals.Results: Baby massage is beneficial for the growth and development of babies.Conclusion: This baby massage can be a non-pharmacological therapy that can help increase the baby's appetite, improve the baby's sleep quality, smooth bowel movements, improve the quality of breastfeeding, increase the body's resistance, and reduce the frequency of spitting up in babies.